MODEL PERLINDUNGAN SOSIAL BAGI PENYANDANG DISABILITAS DI KABUPATEN CIANJUR DIKAJI DALAM PERSPEKTIF HAK ASASI MANUSIA - Tanti Kirana Utami (JURNAL ILMIAH LIVING LAW, 2019)
Law Number 39 of 1999 concerning Human Rights regulates the obligations of the State in protecting each of its citizens, including the respect, protection and fulfillment of the rights of persons with disabilities. Persons with disabilities should get the same opportunity in developing themselves through independence as human beings with dignity. Based on the foregoing it is very important to conduct research on persons with disabilities to find out the objective conditions of persons with disabilities in Cianjur district and to find out policies and programs for social protection activities for persons with disabilities. The research method used is normative juridical with descriptive analytical research specifications. The results showed that the condition of persons with disabilities in Cianjur Regency was caused due to birth or illness with various disabilities spread in several districts and social protection for persons with disabilities in Cianjur regency carried out in the form of providing various facilities and social security in stages. The conclusion of this study is the data of persons with disabilities in Cianjur Regency already included including social protection provided by the government. For this reason, it is expected that various facilities and social security will be improved and local regulations made